1996
DOI: 10.1128/aem.62.2.515-521.1996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of earthworm activity on gene transfer from Pseudomonas fluorescens to indigenous soil bacteria

Abstract: We have developed a model system to assess the influence of earthworm activity on the transfer of plasmid pJP4 from an inoculated donor bacterium, Pseudomonas fluorescens C5t (pJP4), to indigenous soil microorganisms. Three different earthworm species (Lumbricus terrestris, Lumbricus rubellus, and Aporrectodea trapezoides), each with unique burrowing, casting, and feeding behaviors, were evaluated. Soil columns were inoculated on the surface with 10 8 cells per g of soil of the donor bacterium, and after a 2-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 33 publications
2
49
0
2
Order By: Relevance
“…ADP inoculation was not detectable on the surface area of the T-RF of 80 bp, reinforcing the possibility of a decline of the inoculated population. This is in agreement with reports in the literature of a 2-log decline observed for Pseudomonas fluorescens (Daane et al, 1996) and Pseudomonas aeruginosa (Glew et al, 1993) 15 days after their inoculation to a soil microcosm. Moreover, we showed that the amount of Atrazine mineralized after Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 93%
“…ADP inoculation was not detectable on the surface area of the T-RF of 80 bp, reinforcing the possibility of a decline of the inoculated population. This is in agreement with reports in the literature of a 2-log decline observed for Pseudomonas fluorescens (Daane et al, 1996) and Pseudomonas aeruginosa (Glew et al, 1993) 15 days after their inoculation to a soil microcosm. Moreover, we showed that the amount of Atrazine mineralized after Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 93%
“…The role of soil animals, including Collembola and earthworms, as providers of hot spots, has been indicated in the above [28,29]. Speci¢cally, work by Thim et al [28], following pioneering work of Daane et al [44], con¢rmed this hot spot for HGT in soil, by providing evidence that earthworms, in particular Lumbricus rubellus, can facilitate the spread of plasmids from Escherichia coli to soil bacteria. Marker-tagged plasmids with di¡erent transfer properties, i.e.…”
Section: Factors A¡ecting Hgt In Soil and Phytospherementioning
confidence: 98%
“…Nonmotile bacteria must rely on passive dispersal, for example, by passing invertebrates. In a very original study, it was demonstrated that earthworm movement in nonsterile microcosms not only resulted in the dispersal of bacteria, but also promoted horizontal gene transfer (HGT) by bringing cells into contact with each other (Daane et al, 1996). In general, habitats where different populations are brought into close proximity or contact will promote HGT (Sengeløv et al, 2000).…”
Section: Does the Heterogeneity Of The Soil Matrix Promote Diversity?mentioning
confidence: 99%